Improving Students’ Writing Skill Through Dictation Technique (A Classroom Action Research at the Seventh Grade of SMPIT Al Ishmah Academic Year 2024/2025) - Taswadi (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This research of this thesis has been done at SMPIT Al Ishmah. The purpose of this thesis is to find the result of the Improving Students’ Writing Skill Trhough Dictation Technique. Based on the problem that the writer found, Many students’ seem weakness in writing English. The writer thought that by join Dictation technique, can make students more creative and active to study English, especially writing skill. The research method is an classroom action research method that gives description explanation and sentence dictation. It has developed in three cycles, and every cycle has four steps. They are planning, action, observation, and reflection. On the other hand, there uses the collaboration with some inform, like English teacher etc. Every cycle give us information that can be analyzed. The subject of the research in the students’ seven grade of SMPIT Al Ishmah that contains 33 students. The results are based on the explanation of every cycle are available. It can be said to increase students' writing skill is 93.34%. This means that trough Dictation Technique can improves students' writing skill. Based on explanation above, the researcher conclude that The dictation technique has influence toward students’ achievement in their writing. It can be one of methods to improve students' writing skill at SMPIT Al Ishmah.